2022
DOI: 10.1017/s1355617722000704
|View full text |Cite
|
Sign up to set email alerts
|

Utility of empathy informant report in FTD differential diagnosis

Abstract: Objective: Loss of empathy is a hallmark feature of behavioral variant frontotemporal dementia (bvFTD). Change in socioemotional functioning identified by others is often the primary initial presenting concern in this disorder, in contrast to more subtle early cognitive changes and limited patient insight. The present study examined the predictive utility of an empathy informant-report measure for discriminating clinician-diagnosed bvFTD from other dementia syndromes. Method: Data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The remaining 91 studies were rated low quality according to the QUADAS-2 appraisal. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]52,[54][55][56][57][58][59][60][61][62][63][64][102][103][104][105][106]…”
Section: Results From Low-quality Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 91 studies were rated low quality according to the QUADAS-2 appraisal. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]52,[54][55][56][57][58][59][60][61][62][63][64][102][103][104][105][106]…”
Section: Results From Low-quality Studiesmentioning
confidence: 99%
“…The titles and abstracts were reviewed, with 633 articles identified that potentially met inclusion criteria. These articles were then reviewed in full, yielding 96 articles that met eligibility criteria 15–110 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations